EDUCATIONAL PHILOSOPHY OF JIDDU KRISHNAMURTI WITH SPECIAL REFERENCE TO PEACE EDUCATION - Aadil Hussain Mir; Rafiyah Rasool (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The objective of this paper looks at educational philosophy and concept of peace and peace education of the most influential Indian philosopher jiddu krishnamurti. He thought that knowledge about life and ourselves is gained at both the beginning and the end of education. The nourishment of kindness is education, and goodness cannot flourish in the presence of fear. Krishnamurti gives the unique concept of peace and peace education and how it can be used as a weapon to end the conflicts and violence throughout the world. In this paper investigator used the philosophical method and for the data collection primary and secondary sources are used. Overall the study reflected krishnamurti’s educational philosophy for the balanced development of the child. As per krishnamurti Peace cannot be attained by any philosophy or via legislation; it can only be attained when each of us starts to comprehend how our own minds work. If we wait for some new system to bring about peace instead of taking personal responsibility, we will only end ourselves as its slaves.